PENINGKATAN HASIL BELAJAR MATA KULIAH AUDITING II PADA MAHASISWA D3 AKUNTANSI UNESA MELALUI PEMBELAJARAN LANGSUNG - Rohmawati Kusumaningtias, ; Hariyati, (Pendidikan Ekonomi, 2009)
Auditing is the  reverse process of accounting cycle , that is, tracing from financial report to transaction evidence. The process of teaching Auditing, therefore, has the lecturer explain clearly, demonstrate accurately, and perform a model, monitor, and give exercise and  feed back. The method of teaching suitable for this course is direct instruction. This study is aimed to enhance the D3 students UNESA in auditing skill a financial report of a company through direct instruction. The target was that an individual student  learning mastery (score > 65) and the classical learning mastery (e 80 of all students) were achieved. The research showed that the students score increased continuously and the target was reached. In the first cycle 54, 55 % of the students gained B, in the second and the third cycle 72,73 % and 81, 82 % respectively.